Clinicopathological Profile and Outcome of Dengue Fever: A Tertiary Care Hospital Experience (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Introduction: Diverse manifestation of recent dengue outbreak has posed a challenge to pre-existing nature of dengue virus infection and management. This study was designed to observe clinicopathological profile and analyze the diverse presentation and outcome of dengue syndrome in recent outbreak in Bangladesh. Methods: This was a hospital based observational study, carried out in Medicine department of Combined Military Hospital (CMH) Dhaka cantonment in between May and September 2019. Total 300 laboratory-confirmed dengue cases aged more than 11 years presenting within 7 days of symptom onset were studied. Patients who presented 7 days after the onset of symptoms or those who were transferred to other hospitals were excluded from study. Results: Total patients were 300 with male predominance (187, 62.3%) and mean age±SD was 37.6±7.5years with age range 12 to76 years; common presentations were fever (300, 100%),headache (265, 88.3%), skin rash (197, 65.7%), bodyache (186, 62.0%),vomiting (152, 50.7%), diarrhoea (65, 21.7%),abdominal pain (58, 19.3%), and bleeding manifestation (36, 12.0). Eighty four (28%) patient had classical dengue fever (DF), 61 (20.3%) had dengue haemorrhagic fever (DHF), 45(15%) had dengue shock syndrome (DSS) and 110(36.7%) had expanded dengue syndrome(EDS). Relevant investigations showed 157(52.3%) patients had leukopenia,18(6%) had leukocytosis, 254(84.7%) had thrombocytopenia with lowest platelet count 1x109/L,135(45%) had abnormal ALT, 110(36.7%) had abnormal AST, 84(28%) had hyponatraemia,43(14.3%) had AKI,125(41.7%) had pleural effusion with 36(12%) bilateral;102(34%) had ascites, 25(8.3%) developed acalculous cholecystitis;7(2.3%) patient developed cerebrovascular accident. Eighteen (6%) patients required mechanical ventilation and 15 (5%) patients required haemodialysis. Regarding outcome, 5 (1.7%) patients died and 295 (98.3%) patients survived. Conclusion: Dengue fever was presented with common as well as other features and involved a number of organs including liver, kidneys, brain, pleura, peritoneum, and gall bladder and had diverse manifestations and adverse outcome.J Bangladesh Coll Phys Surg 2021; 39: 213-219